Multitargeting for biological control of sleeper weeds - Groenteman, R.; Kelly, D.; Fowler, S.V. (New Zealand Plant Protection, 2008)
Sleeper weeds are weeds at the early stage of invasion exotic species that have become naturalised and are highly likely to turn invasive in due course New Zealand has more naturalised exotic vascular plant species than natives many of which are considered sleeper weeds Biological control is more likely to succeed on weeds that have not yet fulfilled their invasive potential hence its significance in management of sleeper weeds Multitargeting is suggested here as a new approach for safe and effective management of multiple closely related invasive and sleeper weed species from groups not represented in the native flora using agents with a relatively wide host range While specifically targeting an invasive species in the group such agents could prevent closely related sleeper weeds from becoming a problem in the first place Thistles were used as a case study and strong support was found for the multitargeting approach Thus three nontarget less preferred thistle species were attacked and damaged by the biocontrol agent Rhinocyllus conicus more in the presence of its preferred host Carduus nutans (nodding thistle) than in its absence both in a field experiment and in a field survey